PERBEDAAN PENGETAHUAN DAN SIKAP ANAK SEKOLAH DASAR TENTANG KARIES GIGI MELALUI MEDIA BOARD GAME “TOOTH TACTIC” DI SD QUR-AN ARRISALAH KOTA PADANG - Cantika Verinaanwar; Rapitos Sidiq; Evi Maria L Silaban; John Amos; Novelasari Novelasari (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2026)
Background : Dental caries is one of the most common health problems among school-age children and can affect their quality of life. The 2023 SKI reported that 56.9% of Indonesia’s population experienced complaints related to oral and dental health. Screening data from Puskesmas Air Dingin revealed that the highest prevalence of dental caries was found at SD Qur-an Arrisalah. Purpose: This study aimed to determine the differences in knowledge and attitudes of elementary school students regarding dental caries through the educational board game “Tooth Tactic” at SD Qur-an Arrisalah, Padang. Methods:A mixed-method approach was applied, combining a quantitative quasi-experimental one-group pretest-posttest design with a qualitative exploratory approach. The study sample consisted of 57 fifth-grade students selected using proportional random sampling. Data were statistically analyzed using the Wilcoxon test with SPSS. Results:The results showed a significant improvement in students’ knowledge and attitudes after the intervention using the board game. The median knowledge score increased from 10 to 16, while the median attitude score increased from 44 to 66 (p < 0.001). Conclusion: In conclusion, the study demonstrated significant differences in elementary students’ knowledge and attitudes toward dental caries after receiving education through the “Tooth Tactic” board game.